2020
DOI: 10.1097/jom.0000000000001858
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors and Tobacco Use Among Commercial Truck Drivers

Abstract: Objectives: To explore the relationships between tobacco, social support, job satisfaction, and depression among truck drivers. Methods: Cross-sectional data were collected from 797 truck drivers in six US states. Data collected included self-reported medical history and biological samples. Modified Zung depression scale and Work Apgar scores were used to measure depression and social support. Adjusted logistic regression models were used to calculate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Steptoe’s research on the interplay between stress perception, social support, and health behaviors revealed a noticeable uptick in traditional cigarette smoking during stressful times, particularly among students with insufficient social support ( 37 ). Similar patterns have been noted among commercial truck drivers ( 38 ) and adolescents ( 39 ), with those experiencing lower levels of social support showing a higher propensity to smoke. Managing stress, anxiety, boredom, or loneliness is one of important motivators for tobacco use among the youth.…”
Section: Discussionsupporting
confidence: 66%
“…Steptoe’s research on the interplay between stress perception, social support, and health behaviors revealed a noticeable uptick in traditional cigarette smoking during stressful times, particularly among students with insufficient social support ( 37 ). Similar patterns have been noted among commercial truck drivers ( 38 ) and adolescents ( 39 ), with those experiencing lower levels of social support showing a higher propensity to smoke. Managing stress, anxiety, boredom, or loneliness is one of important motivators for tobacco use among the youth.…”
Section: Discussionsupporting
confidence: 66%
“…1,3 Older drivers have had prolonged exposure to risk factors such as a sedentary lifestyle and smoking and more time to develop colorectal polyps and cancer-causing mutations. 1,7,[12][13][14]17,18 Due to the increased exposure to CRC risk factors among truck drivers 12,15,24 amplified awareness and education about the importance of early-detection screening for CRC may aid in reducing CRC morbidity and mortality in this population.…”
Section: Discussionmentioning
confidence: 99%
“…7,[12][13][14] Obesity and tobacco use are twice as high among truckers as they are in the overall U.S. adult labor force, 15,16 and previous research has shown that truck drivers often smoke cigarettes to stay awake. 1,17,18 Truck drivers also often have few nutritious options available to them while commuting, 19 face challenges to eating healthily, 20 and have high rates of metabolic syndrome. 21,22 High-fat diets have been associated with poor health among truck drivers.…”
Section: Purposementioning
confidence: 99%